Urgency of STEM Learning Application in Early Childhood Education: A Review of Literature - Dara Rosita; Sitti Muliya Rizka (SEA-CECCEP, 2023)
The issue of the existence of the technological revolution 4.0 in a mid-Indonesian society, especially Aceh, encouraged educators to continue to transform the education system. It is, of course, related to the challenges of teachers' readiness, including early childhood teachers, in shaping a smart and intelligent generation of Aceh in the global industrial era of 2045. In the future, each generation of Aceh will become a public need and is expected to be able to compete from all sides of life both locally and internationally. With the rapid development of appropriate technology in education, the skills of early childhood teachers are needed in modifying learning. Thus, it can sharpen the mind of students in the fields of science, technology, language, and art. Based on today's data, education in Aceh is left behind in other regions in Indonesia. This is far from the reality and expectation of the motto "Aceh Carong". This phenomenon continues to motivate educators to renovate and find solutions until the education system can educate its generation according to technological needs. The application of the STEM approach is seen as an innovation in modern education to improve scientific and creative thinking skills. This literature study can answer the objectives, potential, and challenges of STEM application in early childhood education. The study findings are also expected to increase teacher understanding of the importance of applying this approach in early childhood learning and to support the practice of teacher professional development in the future.